A holistic approach to understanding retirement preparedness - Yook, Miyoung (Kansas State University, 2014)
There has been increased interest in understanding the significant disparity in U.S. households’ retirement preparedness due to concern about the stability of Social Security benefits, the shift from defined benefit plans to defined contribution plans, and the decreased rate of saving. This dissertation explores a model that can be utilized to understand and enhance retirement preparedness by individuals, educators, practitioners, and policy makers. Retirement preparedness was measured in two different ways—using the income replacement rate and the capital accumulation ratio—for two separate empirical models. The general conceptualization of the framework is based on the retirement planning work of Hershey (2004). This study utilized the 2008 Rand version (Version L) of the Health and Retirement Study (HRS) and 2006, 2008, and 2010 psychosocial and lifestyle questionnaire. The Rand HRS data file is a user-friendly version of the HRS data and contains cleaned data. The two hierarchical regressions were used to analyze the association between retirement preparedness and the theoretical concepts of cultural influence, environmental influence, task components, and psychological influence. Entering the conceptual components as four separate blocks allows for observation of changes in R[2] based on the addition of the conceptual components. This research investigates the following research questions: (a) How strongly are cultural influences associated with retirement preparedness?, (b) How strongly are environmental influences associated with retirement preparedness?, (c) How strongly are task components associated with retirement preparedness?, and (d) How strongly are psychological influences associated with retirement preparedness? Current retirement planning practices are often based on structural profiles such as financial resources, financial needs, and goals. The holistic approach used for this dissertation is based on the awareness of the influence of psychological and personal factors on financial decision making. The results showed that the variables positively associated with the retirement income replacement rate were self-perception of aging, homeownership, stock ownership, household pension ownership, IRA/Keogh ownership, and business ownership. Pre-retirement income log had a highly negative association with the retirement income replacement ratio. Big Five personality and perceived mastery were not significant. However, when asset ownership (excluding homeownership) was not controlled, conscientiousness and low emotional stability became significant and showed a positive association for conscientiousness and a negative association for low emotional stability. Self-perception of aging was a significant psychological variable in both models. The significant variables from the second model measured by the capital accumulation ratio were asset ownerships including homeownership, stock ownership, IRA ownership, real estate ownership, and business ownership. None of the psychological variables were significant, except for agreeableness, which was related negatively to the capital accumulation ratio when the asset ownerships (excluding home ownership) were not controlled. Other significant variables, when asset ownership was not controlled, were home ownership, pre-retirement income log, being non-White.
Keywords: Retirement preparedness; Holistic approach; Psychological factors; Individual & Family Studies (0628)